IMPROVED WOUND HEALING ACTIVITY THROUGH SYNERGISTIC APPROACH OF PUMPKIN SEED OIL AND CURCUMIN LOADED MODEL IN MICROGEL - RAJAPPA, MARGRET CHANDIRA; KANNAN, AJITH; VENKATASUBRAMANIAM, NAGASUBRAMANIAN; VENKATACHALAM, LOKESH; KARNAN, SELVARAGAVAN; ANTONYSAMY, DOMINIC (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to develop a curcumin microgel with lipophilic encapsulation using pumpkin seed oil to enhance wound healing. Methods: Curcumin was analyzed using ultraviolet-visible (UV-Vis) spectrophotometry, and microgels (CP1-CP6) were formulated with pumpkin seed oil encapsulation. Physicochemical tests were performed, and the optimized formulation was selected based on diffusion kinetics. The optimized formulation was subjected to wound healing studies through scratch wound heal assay. Results: The calibration curve of curcumin showed a correlation coefficient>0.973. Drug-excipient studies revealed excellent compatibility. The optimized formulation, CP5 had the lowest zeta potential and highest viscosity, spreadability, and extrudability. CP5 released 94.59% of curcumin in 8 h, following the Korsmeyer-Peppas model. The minimum effective concentration promoting complete wound healing was 50µg/ml in L6 cell lines. CP5 remained stable for three months at 40±2 °C/75±5% RH. Conclusion: Pumpkin seed oil effectively encapsulated curcumin, enhancing its wound healing potential. This microgel formulation showed promise for pharmaceutical applications, and future studies can investigate its pharmacodynamics and wound healing mechanisms.